A Comparison of Cultural Awareness Directives in Junior Middle School English Textbooks and Teacher’s Books of Go for It and English in Mind - Yuanyuan, Liu (International Journal of Humanities and Education Development (IJHED), 2024)
Based on the CAB model of intercultural communication competence(ICC), this paper analyzes the cultural awareness(CA) directives of junior middle school English textbooks and teacher’s books of Go for It (GFI) and English in Mind(EIM) through the methods of text analysis and comparative analysis. The study focuses on the teaching activities of reading, listening, speaking, writing and culture in mind, etc. of the two editions of textbooks and teacher’s books. During the research process, it has been found that firstly, as for the textbook of GFI, the proportion of the three dimensions is ranked in descending order as follows: cognitive dimension first, behavioral dimension second and affective dimension third. The proportion of cognitive dimension is close to that of behavioral skills. The proportions of both cognitive and behavioral dimension are much larger(8 to 10 times) than that of affective dimension. Second, as for the teacher’s book of GFI, the descending order of the three dimensions is the same as in the textbook of GFI. The proportion of cognitive activities is far greater than that of affective and behavioral activities. The proportion of affective activities in both the textbook and the teacher’s book of GFI is very low. Thirdly, as for the textbook of EIM, the proportion of the three dimensions is ranked in descending order as follows: behavioral dimension first, cognitive dimension second and affective dimension third. The proportion of cognitive activities is relatively close to that of behavioral activities. The proportions of cognitive and behavioral activities are more than twice as much as that of the affective activities, which may show that the textbook of GFI pays more attention to the cultivation of students’ cognitive and behavioral abilities, ignoring the cultivation of students’ affective ability. However, compared to the textbook of GFI, the proportion of affective activity in the textbook of EIM is 3 times as that in the textbook of GFI, indicating that the textbook of EIM pays more attention to cultivating students’ affective ability than the textbook of GFI. Fourthly, as for the teacher’s book of EIM, the proportion of behavioral activities is far greater than that of cognitive and affective activities. The data seems to demonstrate that the teacher’s book of EIM has carried out a detailed and in-depth discussion of behavioral activities and paid great attention to the cultivation of students’ behavioral skills. Finally, through comparative study, it has been found that GFI can gain some advisable suggestions on how to write cultural awareness directives by referring to EIM.